Closed-loop neuromodulation for studying spontaneous activity and causality. Issue 4 (April 2022) - Ramot, Michal; Martin, Alex
Abstract : Having established that spontaneous brain activity follows meaningful coactivation patterns and correlates with behavior, researchers have turned their attention to understanding its function and behavioral significance. We suggest closed-loop neuromodulation as a neural perturbation tool uniquely well suited for this task. Closed-loop neuromodulation has primarily been viewed as an interventionist tool to teach subjects to directly control their own brain activity. We examine an alternative operant conditioning model of closed-loop neuromodulation which, through implicit feedback, can manipulate spontaneous activity at the network level, without violating the spontaneous or endogenous nature of the signal, thereby providing a direct test of network causality. Highlights: The focus on clinical applications has obscured the potential of closed-loop neuromodulation as a tool for basic science research. Closed-loop neuromodulation is a flexible neural perturbation tool which can be used to directly reinforce spontaneously emerging brain states of interest. The focus on influencing spontaneous, naturally occurring endogenous activity sets closed-loop neuromodulation apart from other neural perturbation techniques which invariably involve unnatural external interference. The use of closed-loop neuromodulation to directly modulate spontaneous activity may provide a window into its function. The shift from clinically oriented research to a basic science approach requires that we rethink our view of closed-loop neuromodulation, its basic mechanism, the conceptual differences between explicit and implicit feedback, and the role of volitional control in the process.